HUBUNGAN KEKUATAN OTOT LENGAN DAN BAHU DAN KORDINASI MATA TANGAN DENGAN KETERAMPILAN PASING BAWAH DALAM PERMAINAN BOLA VOLI PADA SISWA YANG MENGIKUTI EKSTRAKURIKULER SMK NEGERI 5 PEKANBARU - Hendrik, Hendrik; Ramadi, Ramadi; Vai, Aref (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Based on the author's observations in the field of volleyball for students who take extracurricular activities, the authors observed that it was found that the lower pass was not optimal in volleyball, using arm and shoulder muscles and hand eye coordination. The purpose of this study was to determine the relationship between arm and shoulder muscle strength and hand eye coordination with under-passing skills in volleyball for students who take extracurricular activities at SMK NEGERI 5 PEKANBARU. The population in this study were extracurricular activities at SMK Negeri 5 Pekanbaru who were registered or participated in training, after the survey researchers went directly to the field and based on the information received, the number of active players was 17 people. By using total sampling technique, the entire population is sampled. The instruments in this study were expanding dynamometer to determine the strength of the arm and shoulder muscles, throw grasping the wall to determine hand eye coordination and underpass. The data obtained were analyzed using correlation. Based on the results of research and data processing using statistical research procedures, it is concluded that there is a relationship between arm and shoulder muscle strength with the under-passing ability of the men's volleyball team at SMK Negeri 5 Pekanbaru, this can be seen from the effect given, which is 40.96%. There is an eye-hand coordination relationship with the under-passing ability of the men's volleyball team at SMK Negeri 5 Pekanbaru, this can be seen from the effect that is given, which is 25.40%. There is a relationship between eye-hand coordination and arm and shoulder muscle strength with the under-passing ability of the men's volleyball team at SMK Negeri 5 Pekanbaru, this can be seen from the effect given, which is 42.64%.Keywords: Eye-Hand Coordination, Arm and Shoulder Muscle Strength, Lower